(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the distinctive lexical units characteristic of English national sports—football, rugby, cricket, and tennis—and explains their linguistic value for lexicology, terminology studies, and discourse analysis. The paper treats sport terms as a culturally embedded terminological subsystem shaped by standardization, institutional rulebooks, and media circulation. Using a qualitative linguistic approach, it analyzes (i) term formation mechanisms (compounding, conversion, clipping, and acronymy), (ii) semantic organization (polysemy, specialization, and metaphorization), and (iii) pragmatic-discursive functions (identity marking, evaluation, and stance). The analysis demonstrates that many sport-specific units operate as stable technical designations inside the sport domain while simultaneously generating widely shared idioms in public discourse (e.g., political and business commentary). The study concludes that English national sports terminology is not merely a register-bound vocabulary but a productive lexical resource whose meanings and stylistic values are negotiated across professional, media, and everyday communication.